DUKUNGAN SOSIAL HUBUNGANNYA DENGAN MOTIVASI MENJADI COSPLAYER PADA COSMIC (COSPLAYER MINANG COMMUNITY) PADANG - Darwan, Mukhlisan; Syahrina, Isna Asyri; Okfrima, Ria (PSYCHE 165, 2019)
ABSTRACT   The purpose of this research is to find out whether there is a relationship between social support and motivation to become a cosplayer in COSMIC (cosplayer Minang Community) in Padang. The independent variable in this study is social support and the dependent variable is the motivation to be a cosplayer. The measuring instrument used in this study is the scale of social support and the motivation scale of being a cosplayer. The population in this study amounted to 47 people. The sample technique in this study used a saturated sampling technique. Saturated sampling is a sampling technique if all members of the population are used as samples. Samples in this study amounted to 47 people. Test the validity and reliability usingTechnique Cronbach Alpha. The item different power index on the social support scale moves from 0.337 to 0.793, while the motivation scale becomes a cosplayer moves from 0.330 to 0.741. The reliability coefficient on the social support scale is 0.890, while the reliability coefficient on the motivation scale becomes cosplayer at 0.893. Hypothesis test results show the correlation coefficient of 0.296 with a significant level p = 0.043 means that there is a significant relationship between social support and motivation to become cosplayers in Padang, with the effective contribution of social support to motivation to become cosplayers in Padang by 9% and 91% influenced other factors. So there is a relatively low relationship between social support variables and the motivation to become cosplayers.   Keywords : Social support, Motivation, Cosplayers